(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Forced marriages are worldwide phenomena andalso exist in Pakistani society. It involves the lack of free and full consentof at least one of the parties to a marriage. Mostly, females are victims offorced marriages. It is prevalent in the name of religion in many Muslimcountries; however, it is purely a traditional and cultural phenomenon which hasnothing to do with religion. Forced marriages are different from arrangedmarriages in which both parties freely consent to enter into marriage contractand they have no objection on the choice of partner selected by their parents. This paper explores ways ofaddressing concerns about forced marriage among women who originate from theIndian subcontinent. As first- and second-generation immigrants, these womenface the challenge of negotiating tradition, culture, and honor with increasedindependence, often due to increased educational achievements and economicopportunities. Although the more dramaticcases of forced marriage involve abduction and physical violence, other casesmay be subtler. For the purpose of this paper, forced marriage is defined as a unionbetween two individuals, of whom at least one has not provided consent. Such aunion lies on a continuum of arranged marriages, defined by degrees of coercionand consent. It may therefore be useful to this practice in the larger contextof violence against women in Islamic societies, especially as it relates tocrimes of honor.